PERAN AGEN PERUBAHAN DALAM PENGEMBANGAN MASYARAKAT LOKAL YANG BERKELANJUTAN - Aldim (GoAcademica Research dan Publishing, 2020)
This article discusses the importance of social capital as a key indicator of people's ability to engage in sustainable development, because social capital can have a deterring and facilitating effect. Change agents are expected to enable individuals or groups to increase access to other forms of critical capital to overcome obstacles and solve problems. Bonded social capital consists of strong network ties as negative in excess of numbers because it can lead to the enforcement of social norms that inhibit innovative change, and connecting social capital consisting of weak network ties as a benefit that allows actors to make social changes that are critical. Society achieves change through a dynamic mix of bonding and connecting bonds.